The impact of epilepsy and antiseizure medications on pregnancy and neonatal outcomes: A nationwide cohort study - Cheng‐Yen Kuo; Chang‐Fu Kuo; Lai‐Chu See; Meng‐Jiung Chiou; Po‐Cheng Hung; Jainn‐Jim Lin; Kuang‐Lin Lin; Huei‐Shyong Wang; I‐Jun Chou (Brain and Behavior, 2023)
Abstract Purpose Our objective was to assess the adverse outcomes during pregnancy, as well as for the fetus and neonates, in women with epilepsy, both with and without the use of antiseizure medications (ASMs). Methods A cohort of singleton pregnancies between January 1, 2004 and December 31, 2014 was identified using the Taiwan National Health Database. The pregnancies were categorized into ASM exposure, ASM nonexposure, and control (consisting of women without an epilepsy diagnosis) groups. We recorded adverse outcomes in neonates and documented pregnancy complications. The generalized estimating equation with logit link was used to estimate adjusted odds ratios. Results There were 629 singleton pregnancies in the group exposed to ASMs, 771 in the epilepsy group without ASM exposure, and 2,004,479 in the control group. Women with epilepsy had a significantly higher risk of puerperal cerebrovascular diseases (adjusted odds ratios in the exposure and nonexposure groups = 54.46 and 20.37, respectively), respiratory distress syndrome (5.1 and 2.99), mortality (3.15 and 3.22), sepsis (2.67 and 2.54), pregnancy‐related hypertension (1.71 and 1.8), preeclampsia (1.87 and 1.79), cesarean delivery (1.72 and 2.15), and preterm labor (1.38 and 1.56). The use of ASMs may increase the risk of eclampsia (adjusted odds ratio = 12.27). Compared to controls, fetuses/neonates born to women with epilepsy had a higher risk of unexplained stillbirth (adjusted odds ratios in the exposure and nonexposure groups = 2.51 and 2.37, respectively), congenital anomaly (1.37 and 1.33), central nervous system malformation (3.57 and 2.25), low birth weight (1.90 and 1.97), and a low Apgar score at 5 min (2.63 and 1.3). The use of ASMs may introduce an additional risk of small for gestational age; the adjusted odds ratio was 1.51. Conclusion Women with epilepsy, irrespective of their exposure to ASMs, had a slightly elevated risk of pregnancy and perinatal complications. Puerperal cerebrovascular diseases may be a hidden risk for women with epilepsy.